Dandelion root extract affects ESCC progression via regulating multiple signal pathways. Issue 19 (3rd September 2021) - Duan, Xiaofang; Pan, Limin; Deng, Yuying; Liu, Ya; Han, Xue; Fu, Han; Li, Yuxi; Li, Ming; Wang, Tianxiao
Abstract : Dandelion root extract (DRE) exhibits anti-ESCC activity. Abstract : Dandelion, a medicinal and edible plant, exhibits anti-inflammatory activity. The purpose of the present study was to investigate the inhibitory effectiveness of the aqueous dandelion root extract (DRE) on esophageal squamous cell carcinoma (ESCC). The in vitro cell proliferation, migration, invasion and apoptosis and the in vivo tumor growth were evaluated. The effects of DRE on PI3K/Akt and Ras/Raf/ERK pathways, which are important signaling pathways related to the development and progression of esophageal squamous cell carcinoma, were studied. The effects of DRE on the expression of apoptosis-related proteins BCL2 and BAX were also investigated. Meanwhile, the role of a cystathionine-β-synthase (CBS)/H2 S system in ESCC cells and the effects of DRE on the CBS/H2 S system were assessed. The results showed that DRE selectively inhibited cell growth, proliferation, migration and invasion and induced cell apoptosis in ESCC cells. Moreover, the oral administration of DRE retarded the growth of tumors in human ESCC xenograft models. The DRE treatment led to a dose-dependent reduction in the levels of PI3K, p-Akt, Ras, Raf and pERK1/2 proteins in ESCC cells. DRE also caused a decrease in the anti-apoptotic protein BCL2 and an increase in the pro-apoptotic protein BAX. The data also showed that the CBS/H2 S system implicated in the process of ESCC and DRE inhibited the CBS/H2 S system. Moreover, the CBS knockdown weakened the cancer cell-inhibiting effectiveness of DRE. Therefore, DRE may affect ESCC progression through the regulation of PI3K/Akt and Ras/Raf/ERK signal pathways as well as the endogenous CBS/H2 S system, and consequently, serve as an effective anti-cancer alternative for human ESCC treatment.